Renal function and efficacy of dual antiplatelet vs. alteplase in minor stroke: a post hoc analysis of ARAMIS study - He, Xiao-Yi; He, Chao; Chen, Hui-Sheng (Frontiers in Neurology, 2025)
BackgroundThis secondary analysis of the ARAMIS trial evaluated renal function’s modifying effects on therapeutic responses to dual antiplatelet therapy (DAPT) versus intravenous thrombolysis in acute minor ischemic stroke.MethodsBased on the as-treated set, we stratified patients by admission estimated glomerular filtration rate into three groups: normal renal function (≥90 mL/min/1.73 m2), mildly decreased renal function (eGFR 60 to 89 mL/min/1.73 m2), and moderate to severe impairment renal function group (<60 mL/min/1.73 m2). The primary endpoint was excellent functional outcome defined as a modified Rankin Scale score of 0–1 at 90 days.ResultsAmong 615 analyzed patients, 367 (59.7%) exhibited normal renal function, 209 (34.0%) exhibited mildly decreased renal function and 39 (6.3%) exhibited moderate to severe impairment renal function. A numerically higher rate of excellent functional outcome was found in normal renal function patients with DAPT vs. alteplase (94.4% vs. 90.4%; p = 0.147), while no intergroup difference emerged in mildly decreased renal function patients (93.9% vs. 93.7%; p = 0.958) and moderate to severe impairment renal function patients (93.8% vs. 95.7%; p = 0.792). There was no significant interaction between treatment and renal function on the primary outcome (adjusted interaction p = 0.337).ConclusionAmong patients with normal renal function, DAPT was associated with a numerically higher, but not statistically significant, rate of excellent functional outcome in patients with minor nondisabling acute ischemic stroke presenting within 4.5 h of symptom onset compared with alteplase.Clinical trial registrationClinicalTrials.gov, identifier NCT03661411.